Morfodinâmica da Praia do Cassino, RS - TOZZI, HEITOR AUGUSTO DE MORAES; CALLIARI, LAURO JULIO (Pesquisas em Geociências, 2000)
The Cassino beach morphodynamic oscillates between the dissipative and intermediate states, accumulating sediments in the primary dunes and in long shore bars of combat to South Atlantic Western coastal storms. Approximately five years (1991-1996) of daily littoral environmental observations of wind, waves, long shore currents and beach width allied to coastlines transverse topographical profiles promoted a qualitative methodology which determined the physical agent’s regime and its influences in the sedimentary beach stock and morphodynamic states. Three main incidence angles, South. Southeast (perpendicular to the coastline) and East were characterized in relation to the following factors: wave regime. omega parameter (W = Hb/Tp.Ws) and the mean sea level oscillations. The meteorological tides (storm surges) condition the destruction of the close bars to the beach face and occasionally the frontal dunes. These high wave energy events (hangover) are frequent for the South quadrant (12% a year). The Southeast quadrant (42% occurrences) presents conditions of swell which determine times of dynamic balance of the morphology. These conditions facilitate the development of an intermediary state with long shore bars troughts smaller variations in the sedimentary stock but significant alterations in the bars form. The East quadrant (46% a year) constantly governed by moderate winds and local waves with rare events of swell favours the enlargement to the backshore and coalition of the first bar with the beach face, typical intermediate state of beach in construction. The constructive intermediary state facilitates the largest beach sedimentary variation volume as it becomes more susceptible to strong storms (autumn storms). The dissipative state presents smaller mobility trought the soft slope, leaving the concave beach face, concentrating the storm effect in the surf zone and frontal dunes. We characterized periods of constructive and destructive beach profiles. where the omega parameter evidenced oscillations among the dissipative modal state, of larger frequency in the autumn and winter, and secondary intermediate states in the spring anti summer.